Dense rotational twins in superconducting (111)-orientated δ-NbN epitaxial films on 4H-SiC substrates. (12th March 2021) - Chang, Hsiao-Wen; Ranganayakulu, Vankayala Krishna; Guan, Syu-You; Chen, Peng-Jen; Ou, Min-Nan; Chen, Yang-Yuan; Chuang, Tien-Ming; Chang, Chia-Seng; Wu, Maw-Kuen; Wang, Ming-Jye
Abstract: In order to confirm the superconductivity observed in hexagonal ϵ -NbN reported recently, we have deposited NbN film on (0001) 4H-SiC substrate, with good lattice match, intentionally to grow hexagonal NbN phase. The detailed structural analysis show that the deposited films are (111)-orientated δ -NbN phase with dense rotational (60°) twins. Double diffraction effect in selected area electron diffraction and Moiré fringes in high resolution transmission electron microscope images confirm the existence of rotational twins in nanometer scale. The growth of highly twined film results from no energy preference for the two rotational twins of (111)-orientated δ -NbN to bond with the Si-faced (0001) 4H-SiC substrate. These highly twined δ -NbN epitaxial films exhibit high normal state resistivity, lower T C, but good spatial uniformity of superconducting energy gap. No ϵ -NbN phase was observed in this study which is might due to a low growth temperature of thin film.